2011
DOI: 10.1055/s-0031-1278419
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Changes in Stress Injuries

Abstract: Stress injuries and associated bone marrow changes are a common finding in athletes of all levels. Magnetic resonance imaging (MRI) is the imaging modality of choice for detecting characterizing and staging these injuries. However, because bone marrow edema patterns may also be seen in asymptomatic athletes, it is imperative for the sports medicine physician and the radiologist to closely correlate the imaging findings with the clinical signs and symptoms to assess the clinical significance of the imaging find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…[10] MR imaging plays an important role in the assessment of stress injuries/fractures [Figure 1A–D] due to the relative low sensitivity of radiographs, ranging from 15-35% on initial examination to 30-70% on follow-up examination. [11] Stress fractures are of two types, fatigue and insufficiency. Fatigue fractures are the result of abnormal stress on normal bone structure, whereas insufficiency fractures are the result of a normal stress on an abnormal bone, such as in osteoporosis and osteomalacia.…”
Section: Category I Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] MR imaging plays an important role in the assessment of stress injuries/fractures [Figure 1A–D] due to the relative low sensitivity of radiographs, ranging from 15-35% on initial examination to 30-70% on follow-up examination. [11] Stress fractures are of two types, fatigue and insufficiency. Fatigue fractures are the result of abnormal stress on normal bone structure, whereas insufficiency fractures are the result of a normal stress on an abnormal bone, such as in osteoporosis and osteomalacia.…”
Section: Category I Lesionsmentioning
confidence: 99%
“…The former are more common in young athletes and military recruits and the latter in older patients. [1112] Stress injuries were classified by Fredericson et al . into four grades based on the conventional MR imaging characteristics.…”
Section: Category I Lesionsmentioning
confidence: 99%
“…BMe can be classified into two broad categories: reversible with conservative treatment, such as transient osteoporosis of the hip (TOH), regional migratory osteoporosis (RMO), chronic regional pain syndrome (CRPS), trauma -including stress injuries and insufficiency fractures -and non-reversible, such as avascular necrosis (AVN), infection, tumors, and degenerative and inflammatory arthropathy [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Although MRI is not the method of choice to diagnose a variation in bone deformity, it is considered the imaging modality of choice to diagnose overuse syndromes [9][10]. Kavanach et al, have described the MRI scans of bipartite patella and concluded that bone marrow edema within the bipartite fragment was the only result of knee MRI in almost half of the patients in their series [6].…”
Section: Cases Discussionmentioning
confidence: 99%
“…The initial treatment is non-surgical, consisting of restraint of activity and temporary immobilization. Surgery is only advised in complicated cases where conservative treatment have failed to relieve the symptoms and either excision or stabilization of the unstable bony fragments could be applied [4][5][6][7][8][9][10][11]. In the first case, the patient's non-compliance with the initial treatment and his refusal of a surgical therapy directed us to apply a different therapeutic scheme.…”
Section: Cases Discussionmentioning
confidence: 99%